2018
DOI: 10.1371/journal.pone.0205871
|View full text |Cite
|
Sign up to set email alerts
|

Membrane localization of the Repeats-in-Toxin (RTX) Leukotoxin (LtxA) produced by Aggregatibacter actinomycetemcomitans

Abstract: The oral bacterium, Aggregatibacter actinomycetemcomitans, which is associated with localized aggressive periodontitis, as well as systemic infections including endocarditis, produces numerous virulence factors, including a repeats-in-toxin (RTX) protein called leukotoxin (LtxA), which kills human immune cells. The strains of A. actinomycetemcomitans most closely associated with disease have been shown to produce the most LtxA, suggesting that LtxA plays a significant role in the virulence of this organism. Lt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 54 publications
(64 reference statements)
1
10
0
Order By: Relevance
“…They concluded that the toxin forms a U‐shaped conformation where the N‐terminal hydrophobic region and the C‐terminal region reside on the outside of the membrane, and the central and repeat regions are inside. An immunoblot, using a panel of monoclonal antibodies with epitopes located in varying domains of the toxin, confirmed this result (Brown et al, 2018). Interestingly, the N‐terminal hydrophobic domain, so named because it contains a majority of the hydrophobic residues of LtxA, was not located within the membrane.…”
Section: Host Cell Interactionsmentioning
confidence: 69%
See 2 more Smart Citations
“…They concluded that the toxin forms a U‐shaped conformation where the N‐terminal hydrophobic region and the C‐terminal region reside on the outside of the membrane, and the central and repeat regions are inside. An immunoblot, using a panel of monoclonal antibodies with epitopes located in varying domains of the toxin, confirmed this result (Brown et al, 2018). Interestingly, the N‐terminal hydrophobic domain, so named because it contains a majority of the hydrophobic residues of LtxA, was not located within the membrane.…”
Section: Host Cell Interactionsmentioning
confidence: 69%
“…The toxin has been divided into four functional domains, including an N‐terminal hydrophobic domain (residues 1–420), a central domain (residues 421–730), a repeat domain (residues 731–900), and a C‐terminal domain (residues 901–1,055; Figure 1a). The hydrophobic domain contains most of the hydrophobic amino acids, and has been proposed to play a role in membrane insertion (Lally et al, 1989), although recent results (Brown et al, 2018) call that hypothesis into question, as described in Section 3.6. The repeat domain contains the calcium‐binding, glycine‐rich amino acid sequence (LXGGXGND) that is characteristic of the RTX toxins.…”
Section: Ltxa Expression/secretionmentioning
confidence: 99%
See 1 more Smart Citation
“…For E. coli HlyA several studies showed that the hydrophobic region was responsible for the insertion of the toxin into the target membrane [46,47], and recently it has been reported that its channel-forming domain might contain β-strands, in addition to α-helical structures [48]. In this regard, it has been quite surprising that in the recent publication by Brown et al [49] they suggest that Aggregatibacter actinomycetemcomitans leukotoxin (LtxA) adopts a U-shaped conformation in the membrane, with the hydrophobic N-terminal and the C-terminal (secretion signal) domains residing outside of the membrane. It is thus clear that much remains to be known about the structure of this important domain.…”
Section: Rtx Protein Familymentioning
confidence: 99%
“…The toxin then transverses the cell membrane, binds to the cytoplasmic tails of LFA-1, and causes activation of LFA-1 [30]. Following from the results of the liposomal study LtxA adopts a U-shaped conformation in the membrane, with the N- and C-terminal domains residing outside of the membrane [31].…”
Section: Introductionmentioning
confidence: 99%